The production of sanitary milk - Edwards, Lewis Sidney (My University, 1903)
Introduction: In order to discuss this subject it will be necessary to define a term which has but of late years come into use, and is very differently interpreted by various dairymen. The definition I have chosen may not be the one most largely accepted, but since there is but the one term for different qualities of product we must use the definition rather than the term itself as distinctive. Sanitary milk in this article means, milk produced and handled in such a way, from the cow to the consumer, that it retains its entire high food value and is free from all the dangers which menace our ordinary milk supply. What these dangers are will appear as the different feature of the production of milk are taken up. That the production of such milk is the logical outcome of modern methods and conditions, and is a necessity in the economy of our large cities, it takes but a few words to show. We live under artificial conditions which are extremely trying to the human organism. We spend millions of dollars for hospitals, medicines, doctors and nursing bills. Good common sense demands that we furnish a pure food supply. Milk, the universal food stuff, is more easily contaminated and rendered unwholesome, or absolutely dangerous than any other food material of common use. Except where under the supervision of the proper authorities it is more commonly adulterated than any other food. The increased demand for milk leads to the establishment of large dairies near the centers of population, and in the large dairy the chance for contamination of the product is increased. Extra precautions must then be taken to provide pure milk for general consumption. But it is as food for infants and invalids that milk needs the most careful handling. Reports of Sanitary Boards, Boards of Health and Medical Societies show that much sickness is caused among infants by the presence of bacteria in milk, and that specific disease germs are often carried by this medium.
Citation: Edwards, Lewis Sidney. The production of sanitary milk. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Sanitary Milk; Diseases Carried by Milk; Handling of Milk; Theses